Daily life in Bassarabia in the 1930s: income and expenditures of the local population - Aurel Fondos (Dialogica: Revistă de Studii Culturale și Literatură)
Daily life in Romania in the 30s years, and especially in Bessarabia, represents a period of stabilization, a fact that is evident at the beginning of the return to the context of the Romanian state. On the other hand, this fact is part of the setting of a period in which the economic crisis is highlighted, but also the difficult recovery from the late 1930s. In such a historical context, due to economic developments, the well-being of the population in all Romanian lands was substantially affected, a fact that finds expression in the incomes and expenses of the population, which were largely compromised in the rural environment. The population had to look for alternatives to supplement their income, because they could not live only on the product of cultivating the land and raising cattle. Families are forced to supplement their income through various earnings of non-agricultural origin. Even so, the possibilities of living gathered in this way are so small that they hardly cover the basic needs of the inhabitants. Financial constraints are also attested at the level of local institutions in Bassarabia, which have led to cost reductions and optimizations.